Eyelid sebaceous gland carcinoma: Varied presentations and reconstruction outcome - Raza Rizvi, Syed Ali (Oman J Ophthalmol, 2018)
PURPOSE: To analyze varying clinical presentations, histopathological features, and management outcome of sebaceous gland carcinoma (SGC) of the eyelid. MATERIALS AND METHODS: We retrospectively reviewed medical records of 30 patients with histologically proven cases of SGC of eyelid treated at tertiary care hospital. RESULTS: Patients were in the age group of 28–80 years, among which 18 (60%) were females and 12 (40%) were males. Mean follow-up period was 29.83 ± 8.14 months. Six out of 30 cases were lost to follow-up; hence, only 24 cases were analyzed for reconstruction techniques and management outcome. Initial anatomic sites involved were upper eyelid (10 cases [33.33%]), lower eyelid (5 cases [16.66%]), both upper and lower eyelid (10 cases [33.33%]), and medial canthus (1 case [3.33%]). Orbital extension at presentation was present in 4 cases (13.33%) while metastasis to preauricular lymph nodes was seen in 1 case (3.33%). T2 was the most common category according to TNM staging (14, 58.33%). Reconstruction techniques included direct closure with or without cantholysis in 5 (20.83%), closure with Tenzel's semicircular flap in 2 (8.33%), Cutler Beard repair in 5 (20.83%), and Hughes's flap with either cheek advancement flap or full-thickness skin graft in 3 (12.5%). Both upper eyelid and lower eyelid repair were done in three (12.5%) cases and medial canthal repair in one (4.16%) case. Five (20.83%) cases underwent exenteration. On histopathological examination, 23 (95.83%) patients had localized tumors while only 1 (4.16%) patient had pagetoid invasion. Recurrence was observed in three (12.5%) cases. One (4.16%) case died subsequent to brain metastasis. CONCLUSION: SGC of eyelid may have varied presentations, but early diagnosis and consequent surgical therapy has good outcome and higher survival rate.